The Development of a Standardized Pathway for Outpatient Ambulatory Fracture Surgery: To Admit or Not to Admit. (15th January 2020) - Wolfstadt, Jesse I.; Wayment, Lisa; Koyle, Martin A.; Backstein, David J.; Ward, Sarah E.
Abstract : Background: Increased scrutiny of health-care costs and inpatient length of stay has resulted in many orthopaedic procedures transitioning to outpatient settings. Recent studies have supported the safety and efficiency of outpatient fracture procedures. The aim of the present study was to reduce unnecessary inpatient hospitalizations for healthy patients awaiting surgical treatment of a fracture by 80% by June 30, 2017, with a focus on timely, efficient, and patient-centered care. Methods: The study design was a time series using statistical process control methodology. Baseline data from October 2014 to June 2016 were compared with the intervention period from July 2016 to December 2018. The Model for Improvement was used as the framework for developing and implementing interventions. The main interventions were a policy change to allow booking of outpatient urgent-room cases, education for patients and nurses, and the development of a standardized outpatient pathway. Results: One hundred and eighty-seven patients during the pre-intervention period and 308 patients during the intervention period were eligible for the ambulatory pathway. The percentage of patients managed as outpatients increased from 1.6% pre-intervention to 89.1% post-intervention. The length of stay was reduced from 2.8 to 0.2 days, a decrease of 94.0%. Patient satisfaction remained high, and there were no safety concerns while patients waited at home for the surgical procedure. Conclusions: The outpatient fracture pathway vastly improved the efficiency and timeliness of care and reduced health-care costs. A patient-centered culture and support from hospital administration were integral in producing sustainable improvement. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.